Fasteners in Steel Fiber Reinforced Concrete Subjected to Increased Loading Rates - Boglárka Bokor; Máté Tóth; Akanshu Sharma (Fibers, 2018)
Increased loading rates on fasteners may be caused by high ground accelerations as a consequence of e.g., nuclear explosions, earthquakes or car collisions. It was concluded by Hoehler et al. (2006) that fasteners under rapid loading rates show an increased ultimate resistance in the concrete dominant failure modes or the ultimate resistance is at least as large as under quasi-static loading. Due to the increased demand on using fasteners in steel fiber reinforced concrete (SFRC), it is intended to show how the ultimate concrete cone capacity of fasteners changes under higher than quasi-static loading rate in normal plain concrete (PC) and in SFRC. This paper presents the results of an extensive experimental program carried out on single fasteners loaded in tension in normal plain concrete and in SFRC. The test series were conducted using a servo-hydraulic loading cylinder. The tests were performed in displacement control with a programmed ramp speed of 1, 100, 1000, and 3500 mm/min. This corresponded to calculated initial loading rates ranging between 0.4 and 1600 kN/s. The results of the tension tests clearly show that the rate-dependent behavior of fasteners in SFRC with 30 and 50 kg/m3 hooked-end-type fibers fits well to the previously reported rate-dependent concrete cone behavior in normal plain concrete. Additionally, a positive influence of the fibers on the concrete cone capacity is clearly visible.